Pengembangan Sistem Informasi Wilayah melalui Pembuatan Website dan Plang Denah sebagai Upaya Meningkatkan Akses Informasi Masyarakat di RW 28 Desa Karang Satria - Alghifari Arya Renato; Anggi Setiyowati; Annisa Rachma Tsaniyah; Assyera Adelia Putri; Dinda Safira Syahrani; Emely Laury Simamora; Erka Azaza Adellia; Faishal Nurrohim; Mohammad Revan Afdiansyah; Nadya Shevyani; Nayla Hana Fadilla; Raihan Nur Wahid Hakim; Rendi Kurniawan; Rizky Bagus Endrianto; Tubagus Hedi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of information technology has driven the need for information systems that can provide quick, accurate, and easy access to information for the public. However, in RW 28 Karang Satria Village, information delivery in the area is still done conventionally, making it difficult for residents and newcomers to get information about the area's profile, locations of public facilities, and neighborhood maps. This study aims to develop a regional information system through the creation of a website and map signs as integrated information media to improve public access to information. The methods used include field observation, interviews with RW officials, identifying user needs, system design, website development, and installing map signs in strategic locations. The website was developed using web technology to provide information about the area's profile, organizational structure, news, public services, as well as maps and area layouts that are easily accessible online. Meanwhile, the layout sign serves as a visual information tool that helps residents and visitors get to know the local layout directly. The implementation results show that the information system built can make accessing information easier, assist with navigation around the area, and support transparency in the RW 28 Desa Karang Satria environment. The integration of digital media and physical media provides an effective solution for spreading information to the public. Therefore, developing websites and signboards can be one way to support digital transformation at the village level and improve the quality of information services for the community.